2019
DOI: 10.1002/jcp.28715
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Myb‐induced NF‐kB ‐STAT3 signaling and resulting cisplatin resistance in ovarian cancer by dietary factors

Abstract: c-Myb regulates tumorigenesis in multiple cancers. Here we show, for the first time, the mechanism of c-Myb-mediated proliferation, invasion, and drug resistance in ovarian cancer (OC), the most lethal gynecological cancer, and a comparative analyses of dietary agents, curcumin, epigallocatechin-3-gallate (EGCG), and sulforaphane in inhibiting c-Myb activity. We evaluated myb expression in patients with OC and found its increased expression in patients with cancer, compared with normal controls and in higher g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 30 publications
1
47
1
Order By: Relevance
“…However, the present study demonstrated that EGCG exerted a stronger proliferation inhibition on ovarian cancer SKOV3 cells compared with that on lung cancer A549 cells, although few studies (44,45) have focused on the effects of EGCG on ovarian cancer. Thus, it was meaningful and worthy to study the effects of EGCG on ovarian cancer and explore the underlying molecular mechanism.…”
Section: Discussioncontrasting
confidence: 55%
“…However, the present study demonstrated that EGCG exerted a stronger proliferation inhibition on ovarian cancer SKOV3 cells compared with that on lung cancer A549 cells, although few studies (44,45) have focused on the effects of EGCG on ovarian cancer. Thus, it was meaningful and worthy to study the effects of EGCG on ovarian cancer and explore the underlying molecular mechanism.…”
Section: Discussioncontrasting
confidence: 55%
“…However, c-Myb silencing inhibited proliferation, invasive potential, and sensitized ovarian cancer cells to cisplatin. EGCG completely inhibited c-Myb-mediated proliferative and invasive abilities of ovarian cancer cells [11].…”
Section: Targeting Of Jak/stat Signalingmentioning
confidence: 92%
“…There was higher expression of cytoplasmic STAT1, p-STAT3 (Ser727), STAT5, and nuclear p-STAT3 (Ser727) in the nodes [10]. c-Myb overexpression induced activation of NF-κB and STAT3 signaling to enhance proliferation, invasion, and resistance against cisplatin [11]. However, c-Myb silencing inhibited proliferation, invasive potential, and sensitized ovarian cancer cells to cisplatin.…”
Section: Targeting Of Jak/stat Signalingmentioning
confidence: 97%
“…A protooncogene c-MYB was recently showed to contribute to cisplatin resistance in ovarian cancer 9 and these reported results were the first ever detailing the c-MYBs contribution to proliferation, invasion and development of cisplatin resistance in ovarian cancer cells. One of the key findings of this work was that c-MYB expression is relatively higher in ovarian cancer patients, as compared to normal controls, thus clearly suggesting a role of c-MYB in ovarian cancer pathogenesis.…”
Section: Regulation Of Myb Mediated Cisplatin Resistance Of Ovarian Cmentioning
confidence: 86%
“…Moreover, the expression of c-MYB correlated with higher grade ovarian cancer which suggested a direct relationship between c-MYB expression and aggressive ovarian cancer. The oncogenic role of c-MYB is not limited to ovarian cancer and has been reported in hematological malignancies as well as several solid tumors [9][10][11][12][13] , Despite such wealth of information regarding the oncogenic potential of c-MYB, its role in cisplatin resistance was not known prior to this report 9 . The study reported a connection between c-MYB expression and acquired cisplatin resistance, but there is still no clear understanding regarding how c-MYB can influence cisplatin resistance.…”
Section: Regulation Of Myb Mediated Cisplatin Resistance Of Ovarian Cmentioning
confidence: 93%